2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31972
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-institution Investigation into Faculty Approaches for Incorporating the Entrepreneurial Mind-set in First-year Engineering Classrooms

Abstract: Krista received her B.S. in Aerospace Engineering at The Ohio State University in 2006 and received her M.S. from Ohio State in 2007. In 2012, Krista completed her Ph.D. in Aerospace Engineering at Ohio State. Her engineering education research interests include investigating first-year engineering student experiences, faculty experiences, and the connection between the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Studies in the area of longitudinal EM development often assess students at different curriculum levels at the same time to determine overall progression [9,18,[21][22]. It has been shown that senior level students often showcase greater levels of entrepreneurial interest and curiosity, innovation and design skills, motivation, and making connections than lower level undergraduates [9,[21][22].…”
Section: Longitudinal Em Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in the area of longitudinal EM development often assess students at different curriculum levels at the same time to determine overall progression [9,18,[21][22]. It has been shown that senior level students often showcase greater levels of entrepreneurial interest and curiosity, innovation and design skills, motivation, and making connections than lower level undergraduates [9,[21][22].…”
Section: Longitudinal Em Developmentmentioning
confidence: 99%
“…Research seems to indicate that incorporation of entrepreneurially minded learning (EML) throughout engineering curricula encourages EM growth [13,[32][33], though many studies have addressed the need for more research on the impact of these initiatives [18,31,[33][34]. There are a lack of studies that address longitudinal EM development by following a single cohort of students.…”
Section: Longitudinal Em Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Our first EML-focused efforts included re-structuring the design-build project in our standard sequence of the FYP to more formally include EML concepts. We started that work by visiting other KEEN institutions to learn about their first-year engineering initiatives related to EML [9,10]. We also worked through a backwards design process supported by our teaching and learning center to establish a set of new learning objectives that could guide our curriculum developments moving forward within the first-year and beyond [11,12].…”
Section: History Of Em At Osumentioning
confidence: 99%